Perancangan Perangkat Lunak Teks Editor Bahasa C Menggunakan Metode Lexical Analyzer - Mahmudin Harahap (Graha Mitra Edukasi, 2022)
A computer is a machine that can carry out a set of basic commands (instruction set), so that a computer can do something, we must give it a command that the computer can carry out, namely in the form of a collection of these basic commands. DOS (Disk Operating System) Programming is the name given to programming carried out in the DOS environment, DOS Programming experienced its heyday when the operating system did not have an attractive GUI and did not have a large memory, Turbo C was one of the most widely used programming languages. at the time. Lexical analyzer is a method or technique commonly used to recognize the form of writing, the form of writing here is the commands contained in a programming language, the process of recognizing these commands is of course based on the compiler in the program language used, these commands will be distinguished by functions of existing commands, such as strings, variables, functions and others, this is used to make it easier for programmers to distinguish existing commands. In the Lexical analyzer method the word is called a token, where the Lexical analyzer scans the characters that match the tokens that have been set. The tokens identified in this study are verbs, where the verb consists of pure and verbs that have affixes